1975
DOI: 10.1536/ihj.16.719
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynarnics of Spontaneously Hypertensive Rats in Conscious State

Abstract: SUMMARYCardiac output of unanesthetized spontaneously hypertensive rats (SHR) and normotensive control rats (NCR) was measured by an aortic pressure pulse contour method. A catheter was introduced into the aortic arch under ether anesthesia and aortic pressure curves were recorded after the recovery from anesthesia. Stroke volume was calculated by reading required pressure and time data on the tracings and substituting them into a special equation. Cardiac output per min per body weight was not significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Also in anesthetized SHR, the increase in efferent discharge in the splanchnic nerve was quantitated by IRIUCHI-JIMA (1973). That the sympathetic nerves, in the conscious state as well play an important role in hypertension in SHR was shown by NUMAO et al (1975), who observed normalization of total peripheral resistance by ganglion blockade with hexamethonium. Increased sympathetic discharge in conscious SHR was observed with the splanchnic nerve by JUDY et al (1976) and with the renal nerve by LUNDIN and THOREN (1982) and LUNDIN et al (1984).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Also in anesthetized SHR, the increase in efferent discharge in the splanchnic nerve was quantitated by IRIUCHI-JIMA (1973). That the sympathetic nerves, in the conscious state as well play an important role in hypertension in SHR was shown by NUMAO et al (1975), who observed normalization of total peripheral resistance by ganglion blockade with hexamethonium. Increased sympathetic discharge in conscious SHR was observed with the splanchnic nerve by JUDY et al (1976) and with the renal nerve by LUNDIN and THOREN (1982) and LUNDIN et al (1984).…”
Section: Discussionmentioning
confidence: 87%
“…However, this is due to a larger cardiac index in SHR than in NCR after ganglion blockade. Total peripheral resistance is somewhat lower in the former than the latter after blockade (NUMAO et al, 1975). The larger cardiac index may be ascribable to left ventricular hypertrophy and some possible change in the capacitance section of the circulatory system of SHR (NILSSON and FOLKOW, 1980;.…”
Section: Discussionmentioning
confidence: 87%
“…50 Pentobarbital anesthesia and thoracotomy in the rat produce marked decreases in cardiac output in both SHR and Wistar rats, as well as decreases in aortic pressure in the SHR. 19 Thoracotomy alone can also reduce mean arterial pressure in the SHR up to 48%. 16 Indicator-dilution techniques as used in the study of spontaneous hypertension 11 ' 1J require anesthesia and are further limited by not being capable of measuring transient changes in cardiac output occurring over a short time period.…”
mentioning
confidence: 99%
“…2). The in vivo compliance of the aortic segment of the arterial tree has been determined at 36 x 10 -3 cm 3 kPa -1 (27,31) which compares with the upper section of the model's compliance range (4.5 • 10-~36 • 10 -3 cm 3 kPa -1, Fig. 8).…”
Section: Discussionmentioning
confidence: 99%